Gaú-chê-rama-ura: mito e imaginário no épico de Zulmiro Lino Lermen - Lima, Letícia (My University, 2020)
This dissertation investigates the extent to which the poem entitled Gaú-chê-rama-ura, by the Caxiense writer Zulmiro Lino Lermen, dialogues with the literary tradition of Rio Grande do Sul, incorporating the mythical figure of the gaúcho herói, present in the social imaginary of the State of Rio Grande do Sul and widely disseminated in and through the literature of Rio Grande do Sul. The author, who wrote his work in the late 1960s, deals with the history of Rio Grande do Sul from an epic perspective, going back to the classic epic molds, as well as following a path already traced by romantic regionalism, from which stands out the appreciation of man, the land and culture of the state. This study intends, therefore, to demonstrate how the symbolic elements of this social imaginary from Rio Grande do Sul are incorporated into the text. To this end, an interdisciplinary dialogue is established between Literature, History, and theories about myth and the imaginary. The research takes as theoretical support the discussions of Gilbert Durand (1995; 1997; 2000) and Bronislaw Baczko (1985) about the collective and social imaginary, Mircea Eliade (2002) and Joseph Campbell (2010) about mythology, Emil Staiger abou epic, Guilhermino Cesar (1971), Regina Zilberman (1982; 1985) and Donaldo Schüler (1987) on the history of literature in Rio Grande do Sul and the myth of the gaúcho herói and Tau Golin (1985)and Sandra Jatahy Pesavento (2002) on issues related to the history of Rio Grande do Sul. The results point to the constitution of the poem as an epic that corroborates the permanence of the myth of the gaúcho herói in the imagination and southern literature. [resumo fornecido pelo autor]
Esta dissertação investiga em que medida o poema intitulado Gaú-chê-rama-ura, do escritor caxiense Zulmiro Lino Lermen, dialoga com a tradição literária sul-rio-grandense, incorporando a figura mítica do gaúcho herói, presente no imaginário social do Estado do Rio Grande do Sul e vastamente difundida na e pela literatura sul-rio-grandense. O autor, que escreveu sua obra no final dos anos 1960, tematiza a história do Rio Grande do Sul a partir de uma perspectiva épica, remontando aos moldes das epopeias clássicas, bem como seguindo um caminho já trilhado pelo regionalismo romântico, de onde sobressai a valorização do homem, da terra e da cultura gaúchos. Este estudo pretende, portanto, demonstrar de que modo os elementos simbólicos desse imaginário social sul-rio-grandense são incorporados ao texto. Para tanto, estabelece-se um diálogo interdisciplinar entre Literatura, História e as teorias sobre o mito e o imaginário. A pesquisa toma como suporte teórico as discussões de Gilbert Durand (1995; 1997; 2000) e Bronislaw Baczko (1985) sobre o imaginário coletivo e social, Mircea Eliade (2002) e Joseph Campbell (2010) sobre mitologia, Emil Staiger (1993) sobre o épico, Guilhermino Cesar (1971), Regina Zilberman (1982; 1985) e Donaldo Schüler (1987) sobre a história da literatura sul-rio-grandense e o mito do gaúcho herói e Tau Golin (1985) e Sandra Jatahy Pesavento (2002) sobre questões referentes à história do Rio Grande do Sul. Os resultados apontam para a constituição do poema como um épico que corrobora a permanência do mito do gaúcho herói no imaginário e na literatura sulinos. [resumo fornecido pelo autor]
Keywords: Lermen, Zulmiro, 1917-1997; Contos sul-rio-grandenses - Poesia - Crítica e interpretação; Imaginário; Gaúchos; South-rio-grandense literature - Poetry - Criticism and interpretation; Imaginary; Gauchos